PENYEBARAN SPASIAL KEANEKARAGAMAN TUMBUHAN PANGAN DAN OBAT DI KAMPUNG NYUNGCUNG, DESA MALASARI, KECAMATAN NANGGUNG, BOGOR - Hafizah Nahlunnisa; Ervizal A.M. Zuhud; Lilik Budi Prasetyo (Media Konservasi, 2015)
Nyungcung Kampong is situated near to the forest, thus it is rich in term of plant biodiversity. The plants found in the area potentially can be utilized by the community to meet their needs of food and medicine. The objective of the research was to identify the diversity, potency, and spatial distribution of food and medicinal plants in Nyungcung Kampong. The research was conducted through vegetation inventory and exploration during March 2015. Data analysis was carried out on plant composition, species diversity, evenness, and spatial data analysis. The results indicated that there was differences in diversity value and evenness index among every growth strata. In total, there were 318 plant species that belongs to 98 families, where 56 species of which are food plants, 112 species are food functional plants, and 150 species are medicinal plants. With regard to land cover/land use class, home garden had the highest number of food and medicinal plants (114 species). The plants distributed mostly on elevation of about 600--800 mdpl (308 species) and at gentle slope of about 0-8% (168 species). In addition to slope and elevation, biotic (factor caused by human) have a considerable effect in the distribution of plants. In short, the community needs of necessity food and medicine can be provided by the forest and its surrounding areas.  Keywords: diversity, food and medicinal plants, Nyungcung Kampong, potency, spatial distribution